Seismic Performance Evaluation of Irregular High-Rise Reinforced Concrete Buildings - Parmar, Vastsal; James, Dilip (Journal of Progress in Civil Engineering, 2025)
“Effect of Shear Wall in Seismic Performance of High-Rise Irregular RC Framed Building” considers the effect of introduction of shear wall in a high-rise irregular building. It compares the displacement responses that come about when a high-rise building is subject to lateral loads in an earthquake prone region. Irregular building with and without shear walls with different configurations are analyzed using the IS:456 2000 and seismic code IS:1893 2016. The earthquake loads are analyzed using static (Equivalent Static Method) and dynamic (Response Spectrum) methods as per IS:1893 2016 and the time history method using acceleration time history of Bhuj 2001. Based on the comparisons done during this study, the lateral stiffness of the buildings is enhanced by the introduction of shear walls at the building which leads to better performance against lateral loads. The configuration with shear wall at the lift core gives a good performance against lateral load in both the x and the y directions and the configuration with the shear wall along the y direction gives the best performance against lateral loads in y direction. The performance of any highrise buildings can be improved by providing shear wall of appropriate lengths at appropriate locations. The location should be such that the shear wall should help in decreasing eccentricity, and distributing gravity and lateral loads in best way possible.